Feedback of students on internship program in an agricultural course - Honeylet J. Nicolas; Helen G. Manalastas; Robert A. Capalad (International Journal of Evaluation and Research in Education (IJERE), 2022)
Internship is the essential part of curriculum where students get hands-on experience in training establishments that complement their formal learning in school. Studies on institutional internship programs are done to identify concerns that may hinder its successful implementation. Through the lens of student-interns, this study aimed to assess industry partners and the internship program for undergraduate Animal Science majors, in order to propose strategies toward enhanced internship implementation specifically for the institution’s new curriculum for agriculture students. The study utilized the descriptive-evaluative survey method using an adapted and modified questionnaire. Based on the results, the 217 surveyed student-interns assessed their host training establishments to be very satisfactory in terms of facilities, communication, regard for people, empowerment, and work ethics. They rated the internship program as excellent in overall effectiveness, and very satisfactory in policies. The interns seldom encountered problems while training. The proposed action plan gives strategic options in the areas of linkages and policies, to enhance the overall implementation of the internship program, toward optimized benefits for students, industry partners, and the college. This research can contribute to the improvement of internship in agriculture-related courses in higher education institutions.